2020
DOI: 10.1038/s41598-020-74634-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of rice (Oryza sativa L.: SRNC05053-6-2) crude extract on psoriasis using in vitro and in vivo models

Abstract: Psoriasis is mainly caused because of inappropriate immune responses in the epidermis. Rice (Oryza sativa L.: SRNC05053-6-2) consists of anthocyanin, which exhibits strong antioxidative and anti-inflammatory properties. This study aimed to evaluate the role of this black-coloured rice crude extract in alleviating the symptoms of psoriasis using human psoriatic artificial skin and an imiquimod-induced rat psoriasis model. Psoriasis-related genes, cytokines and chemokines were examined; in addition, the antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…A previous study indicated that the risk of leukemia was reduced after intake of purple rice anthocyanin by increasing the population of white blood cells and promoting macrophage phagocytic activity [ 166 ]. Moreover, the anti-inflammatory properties of anthocyanin extracted from purple rice have been investigated in the treatments of wound healing of psoriasis and oral mucositis in animal models [ 167 , 168 ]. Most recently, anthocyanins isolated from rice husk have been demonstrated to be novel anticarcinogenic compounds in the liver due to their cancer chemo-preventive properties [ 90 ].…”
Section: Significant Roles Of Anthocyanin From Purple Rice In Human Healthmentioning
confidence: 99%
“…A previous study indicated that the risk of leukemia was reduced after intake of purple rice anthocyanin by increasing the population of white blood cells and promoting macrophage phagocytic activity [ 166 ]. Moreover, the anti-inflammatory properties of anthocyanin extracted from purple rice have been investigated in the treatments of wound healing of psoriasis and oral mucositis in animal models [ 167 , 168 ]. Most recently, anthocyanins isolated from rice husk have been demonstrated to be novel anticarcinogenic compounds in the liver due to their cancer chemo-preventive properties [ 90 ].…”
Section: Significant Roles Of Anthocyanin From Purple Rice In Human Healthmentioning
confidence: 99%
“…The rats were shaved on the back (size 3 × 3 cm 2 ) and administered 62.5 mg of imiquimod daily for 7 days to induce psoriasis of the rat skin. 23 , 24 The most effective dose for psoriasis treatment was determined by varying the concentration of sericin treatment and comparing these treatments to the control treatment. For the experiment, the psoriatic rats were divided into six groups (five rats/group).…”
Section: Methodsmentioning
confidence: 99%
“…The rats in each group were separately treated with Vaseline (nontreated group); 2.5%, 5%, and 10% sericin cream (sericin-treated group); 0.1% betamethasone (positive control for the steroid-treated group); and 3 μg/ml calcitriol ointment (positive control for the vitamin D-treated group). 23 All the treatments were continued 2 times/day for 7 days in combination with 62.5 mg of imiquimod to maintain the psoriatic skin. Then, all the rats were humanely sacrificed by overdose carbon dioxide inhalation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations